Determinação de ácidos haloacéticos em água utilizando técnicas cromatográficas - Silva, Claudia Pereira da (2010)
Disinfection is an essential step in water treatment. This step, in most cases, is made by the use of chlorine and its derivatives, which have been quite effective. However, the use of chlorination to disinfect water produces various organic substances, among them, haloacetic acids (HAAs), a total of nine species: monochloroacetic acid (MCAA), dichloroacetic acid (DCAA), trichloroacetic acid (TCAA), monobromoacetic acid (MBAA), acid dibromoacetic (DBAA) tribromoacetic acid (TBAA) bromochloroacetic acid (BCAA), bromodichloroacetic acid (BDCA) and dibromochloroacetic acid (DBCA), which are haloreplaced carboxylic acids, which are toxic to humans, animals and plants. Recent studies have demonstrated an association between the development of some types of cancer with the haloacetic acids. Because of this, the Environmental Protection Agency (EPA) has established for the disinfection by-products a maximum contamination level (MCL) in treated water from 60 μg/L for the sum of five HAAS (MCAA, DCAA, TCAA, MBAA, DBAA ). The World Health Organization (WHO) also established MCL for DCAA (50 μg/L) and TCAA (100 μg/L). However, Brazil and the European Community do not set limits for these species. Therefore, this study aimed to develop an analytical method for the determination of Haas in water, using chromatographic techniques. Tests chromatographic separations were performed by ion chromatography (IC), high performance liquid chromatography (HPLC) and gas chromatography (GC) method development for the analysis of haloacetic acids in water. From the tests there were drawbacks in the analysis when it used IC or HPLC. By carrying out analysis by GC, that was with favorable conditions for the analysis, and a prerequisite for bypass was necessary. When the band worked with 0,5 to 50,0 μg/L were obtained correlation coefficients (r) ranging from 0,98 to 0,99, recoveries in the range 67 to 179%, detection limit of 0,08 to 7,2 μg/L and limit of quantification between 0,2 to 21,6 μg/L for the determination of Haas in water.